Butyrate Protects Barrier Integrity and Suppresses Immune Activation in a Caco-2/PBMC Co-Culture Model While HDAC Inhibition Mimics Butyrate in Restoring Cytokine-Induced Barrier Disruption - Korsten, Sandra G P J; Vromans, Herman; Garssen, Johan; Willemsen, Linette E M (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Low-grade inflammation and barrier disruption are increasingly acknowledged for their association with non-communicable diseases (NCDs). Short chain fatty acids (SCFAs), especially butyrate, could be a potential treatment because of their combined anti-inflammatory and barrier- protective capacities, but more insight into their mechanism of action is needed. In the present study, non-activated, lipopolysaccharide-activated and αCD3/CD28-activated peripheral blood mononuclear cells (PBMCs) with and without intestinal epithelial cells (IEC) Caco-2 were used to study the effect of butyrate on barrier function, cytokine release and immune cell phenotype. A Caco-2 model was used to compare the capacities of butyrate, propionate and acetate and study their mechanism of action, while investigating the contribution of lipoxygenase (LOX), cyclooxygenase (COX) and histone deacetylase (HDAC) inhibition. Butyrate protected against inflammatory-induced barrier disruption while modulating inflammatory cytokine release by activated PBMCs (interleukin-1 beta↑, tumor necrosis factor alpha↓, interleukin-17a↓, interferon gamma↓, interleukin-10↓) and immune cell phenotype (regulatory T-cells↓, T helper 17 cells↓, T helper 1 cells↓) in the PBMC/Caco-2 co-culture model. Similar suppression of immune activation was shown in absence of IEC. Butyrate, propionate and acetate reduced inflammatory cytokine-induced IEC activation and, in particular, butyrate was capable of fully protecting against cytokine-induced epithelial permeability for a prolonged period. Different HDAC inhibitors could mimic this barrier-protective effect, showing HDAC might be involved in the mechanism of action of butyrate, whereas LOX and COX did not show involvement. These results show the importance of sufficient butyrate levels to maintain intestinal homeostasis.
Keywords: PBMCs; butyrate; in vitro models; intestinal epithelial cells; mucosal immunity; short chain fatty acids; Food Science; Nutrition and Dietetics; SDG 3 - Good Health and Well-being